0.013 mm2, kHz‐to‐GHz‐bandwidth, third‐order all‐pole lowpass filter with 0.52‐to‐1.11 pW/pole/Hz efficiency. Issue 21 (1st October 2013) - Chen, Yong; Mak, Pui‐In; Zhang, Li; Qian, He; Wang, Yan
Abstract : A third‐order all‐pole analogue lowpass filter (LPF) with kHz‐to‐GHz bandwidth tunability is proposed. It embeds a current‐reuse active inductor into a current‐scalable source follower to realise three concurrently tunable poles in a single branch. The LPF fabricated in 0.18 μm CMOS measures a tunable − 3 dB cutoff from 0.8 kHz to 1.2 GHz, under a scalable power of 1.25 nW to 4.01 mW. Owing to no tuning capacitor, the die area is extremely compact (0.013 mm 2 ) and the achieved filter efficiency is 0.52 to 1.11 pW/pole/Hz.